Uji toksisitas akut limbah pengeboran minyak (serbuk bor) terhadap Artemia salina - Endang Sriwahyuni; Majariana Krisanti (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
This study aimed to determine acute toxicity of cutting as drilling waste of oil and gas exploration on brine shrimp (Artemia salina) and its influence on the morphology of the test biota. The concentration used in the acute toxicity test namely 22,000, 39,000, 70,000, 126,000 and 226,000 ppm. Acute concentration value (LC50) was estimated by probit methods. The concentration of acute toxicity (LC50) 96 hours of drilling cutting was 34,260 ppm. The test biota responded to exposure of cutting waste, in the form of changes in swimming position, activity, stress level and damage in the morphology and anatomy of the body.